1999
DOI: 10.1161/01.str.30.7.1464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Citicoline Combined With Thrombolytic Therapy in a Rat Embolic Stroke Model

Abstract: Background and Purpose-We sought to evaluate the effects of the combination of cytidine-5Ј-diphosphocholine (citicoline) and thrombolysis on infarct size, clinical outcome, and mortality in a rat embolic stroke model. Methods-Eighty-three Sprague-Dawley rats were embolized in the carotid territory with a single fibrin embolus and randomly assigned to the following treatment groups: (1) control (saline), (2) citicoline 250 mg/kg, (3) citicoline 500 mg/kg, (4) recombinant tissue plasminogen activator (rtPA) 5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
8

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 40 publications
1
48
0
8
Order By: Relevance
“…In another MCA occlusion study, treatment was begun at 15 min after onset of ischemia; citicoline improved behavioral and morphological indices chiefly in rats with submaximal insults (ischemia of 30-75 min) (Aronowski et al, 1996a). When ischemia was produced by clot embolus, one study showed that citicoline begun at 45 min failed to affect infarct size unless tPA was co-administered (Andersen et al, 1999); and another showed that citicoline administered prior to tPA failed to confer additional benefit but, if administered 10 min after tPA, led to less ischemic injury than with tPA alone (Alonso de Lecinana M. et al, 2006). An interesting recent report (Hurtado et al, 2007) provides evidence that citicoline treatment begun 24 hours after MCA occlusion and maintained for 28 days improves functional outcome and enhances dendritic complexity and spine density in layer V pyramidal cells of the undamaged motor cortex, suggesting that chronic treatment may increase neuronal plasticity within noninjured, functionally connected brain regions.…”
Section: Phospholipid Precursor: Citicolinementioning
confidence: 99%
“…In another MCA occlusion study, treatment was begun at 15 min after onset of ischemia; citicoline improved behavioral and morphological indices chiefly in rats with submaximal insults (ischemia of 30-75 min) (Aronowski et al, 1996a). When ischemia was produced by clot embolus, one study showed that citicoline begun at 45 min failed to affect infarct size unless tPA was co-administered (Andersen et al, 1999); and another showed that citicoline administered prior to tPA failed to confer additional benefit but, if administered 10 min after tPA, led to less ischemic injury than with tPA alone (Alonso de Lecinana M. et al, 2006). An interesting recent report (Hurtado et al, 2007) provides evidence that citicoline treatment begun 24 hours after MCA occlusion and maintained for 28 days improves functional outcome and enhances dendritic complexity and spine density in layer V pyramidal cells of the undamaged motor cortex, suggesting that chronic treatment may increase neuronal plasticity within noninjured, functionally connected brain regions.…”
Section: Phospholipid Precursor: Citicolinementioning
confidence: 99%
“…CDP-choline (citicoline) inhibits cPLA 2 activity and lowers the concentration of free fatty acids in a dose-and time-dependent manner (Adibhatla et al, 2002). This compound is an intermediate in PtdCho biosynthesis that has been used for the treatment of ischemic and head injuries (Andersen et al, 1999;Dempsey and Rao, 2003). It not only restores the concentration of PtdCho after ischemic injury by increasing PtdCho synthesis from diacylglycerol but also blocks the activation of cPLA 2 activity (Adibhatla et al, 2002).…”
Section: Use Of Phospholipase a 2 Inhibitors For The Treatment mentioning
confidence: 99%
“…tPA + neuroserpin (an endogenous tPA inhibitor) [25,89,90]. tPA + CDP-choline showed benefit in an animal model of stroke [91]. A high dose of CDP-choline (1000 mg/kg) was better than tPA alone and equally as good as the combination with tPA [92].…”
Section: Fig 2 Blood Clot Formationmentioning
confidence: 99%